A new inequality estimate for urban India? Using house prices to estimate inequality in Mumbai - Gerton Rongen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper applies a novel inequality estimation method to household consumption expenditure in Mumbai, India. Since the richest households may be missing in survey data, this reestimated inequality figure takes them into account by combining survey data with house price data. However, application of this method does not indicate that the survey-based Gini coefficient of 0.447 underestimates consumption inequality in Mumbai; none of the ten investigated scenarios yields a higher estimate. Further analyses are necessary to assess the robustness of estimates and the usefulness of applying this method to the whole of urban India.
Keywords: C81; D31; O15; 330; house prices; India; inequality; top incomes